Pangio lidi, a new species of loach from eastern Borneo, Indonesia (Teleostei: Cobitidae) - Hadiaty, Renny Kurnia; Kottelat, Maurice (Zootaxa, 2009)
Pangio lidi is distinguished from the other species of the P. anguillaris group by the absence of pelvic fins. It is presently known only from the Mahakam River drainage in eastern Borneo.